Depresi pada Pasien dan Masyarakat Terhadap Kejadian Covid-19: Studi Literature - Nova Mardiana; Iyus Yosep; Efri Widianti (Jurnal Medika Cendikia, 2021)
The Covid-19 pandemic is sweeping the world. The increase cases in countries infected of Covid-19 has resulted in the government making policies to prevent Covid-19, including the implementation of social and physical distancing which requires people to stay at home and health workers at the front line. This often causes flatness in various situations and conditions, such as people experiencing a decrease in sleep quality and accompanied by symptoms of anxiety, depression and stress. This study using the literature review method aims to produce a literature review on the relationship between depression in patients and the community with the incidence of Covid-19. The search databases used were Science Direct, Google Scholar, PubMed/NCBI, Elsevier and JHQ (Journal for Healthcare Quality) and Journals from the National Library of Indonesia (PNRI). The keywords used in the search are depression, mental illness, covid-19, physiological effects. 649 articles were identified, then the articles were selected according to the inclusion criteria set based on the PICOS (Population, Intervention, Comparison, Outcomes, Study design) method. The source of the article was clear, published in 2010 – 2020, then checked the feasibility of full text articles conducted on 50 articles. The final results obtained from the selection process are 10 articles that will be carried out in a literature review process. It can be concluded from the results of a literature review that there is still low research that examines the effect of progressive muscle relaxation related to symptoms of depression or other preventive measures to overcome depression in patients and the community during the Covid-19 pandemic.